2021
DOI: 10.1038/s41467-020-20679-y
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3L/NIX-mediated mitophagy protects against glucocorticoid-induced synapse defects

Abstract: Stress-induced glucocorticoids disturb mitochondrial bioenergetics and dynamics; however, instead of being removed via mitophagy, the damaged mitochondria accumulate. Therefore, we investigate the role of glucocorticoids in mitophagy inhibition and subsequent synaptic defects in hippocampal neurons, SH-SY5Y cells, and ICR mice. First, we observe that glucocorticoids decrease both synaptic density and vesicle recycling due to suppressed mitophagy. Screening data reveal that glucocorticoids downregulate BNIP3-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 69 publications
3
63
1
Order By: Relevance
“…Specifically, we tested the SH-SY5Y cells with 0.1, 0.5, 1 and 5 μM of cortisol for 6, 12, 24 and 48 h, to mimic acute and chronic stressors ( Choi et al, 2021 ; Silva et al, 2019 ). As reported in Supplementary Figure 1 , regardless of the cortisol concentrations herein used, Rack1 gene and protein expression were not altered at the earliest time points (6 and 12 h) while we observed a decrease of Rack1 mRNA and protein levels at 24 and 48 h with 1 and 5 μM of cortisol.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we tested the SH-SY5Y cells with 0.1, 0.5, 1 and 5 μM of cortisol for 6, 12, 24 and 48 h, to mimic acute and chronic stressors ( Choi et al, 2021 ; Silva et al, 2019 ). As reported in Supplementary Figure 1 , regardless of the cortisol concentrations herein used, Rack1 gene and protein expression were not altered at the earliest time points (6 and 12 h) while we observed a decrease of Rack1 mRNA and protein levels at 24 and 48 h with 1 and 5 μM of cortisol.…”
Section: Resultsmentioning
confidence: 99%
“…However, during experimentation, subjects were placed individually in filled glass cylinder for a period of 6 min and the total duration of immobility was measured (ANY-maze, Stoelting Co.) as indicative of depressive-like behaviour. Immobility was defined as floating or remaining motionless without leaning against the wall of the cylinder [33].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that NIX (but not BNIP3) is downregulated by stress-induced glucocorticoids, contributing to chronic stress-induced synaptic defects, which has been shown on mouse hippocampal neurons and human neuroblastoma SH-SY5Y cells. This decreased NIX expression is achieved through the binding of the glucocorticoid receptor to PGC-1α, which leads to its downregulation and decreased nuclear translocation, thus decreasing NIX-dependent mitophagy [ 57 ]. Figure 2 presents the scheme of receptor-mediated mitophagy.…”
Section: Mitophagy In Neurons In Aging and Neurodegenerationmentioning
confidence: 99%